Efficacy of surgical navigation in zygomaticomaxillary complex fractures: randomized controlled trial. Issue 9 (September 2022) - Cheng, M.; Zhu, Y.; Liu, Q.; Shen, S.; Qian, Y.; Yu, H.
Abstract: Accurate reduction is of vital importance in the treatment of zygomaticomaxillary complex (ZMC) fractures. Computer-assisted navigation systems (CANS) have been employed in ZMC fractures to improve the accuracy of surgical reduction. However, randomized controlled trials on this subject are rare and the benefits of CANS remain controversial. The aim of this study was to compare reduction errors between navigation-aided and conventional surgical treatment for ZMC fractures. Thirty-eight patients with unilateral type B ZMC fractures were enrolled. Preoperative computed tomography data were imported into ProPlan software for virtual surgical planning. Open reduction and internal fixation was performed with CANS (experimental group) or without CANS (control group). Postoperative computed tomography scans were obtained to examine the difference between surgical planning and the actual postoperative outcome, namely reduction errors. The median translational reduction errors in the X, Y, and Z axes were 0.80 mm, 0.40 mm, and 0.80 mm, respectively, in the experimental group and 0.53 mm, 0.86 mm, and 0.83 mm, respectively, in the control group ( P > 0.05). The median rotational reduction errors in pitch, roll, and yaw were 0.92°, 2.47°, and 1.54°, respectively, in the experimental group and 1.45°, 3.68°, and 0.76°, respectively, in the control group ( P > 0.05). In conclusion, compared with conventional reduction surgery, navigation-aided surgery showed no significant improvement in reduction accuracy in the treatment of type B ZMC fractures (Chinese Clinical Trial Registry, registration number ChiCTR1800015559).